Pojmovanja ustvarjalnosti in stališča do te pri sedanjih in bodočih vzgojiteljicah predšolskih otrok - Dolenc, Petra; Čehovin, Gaja (Revija za elementarno izobraževanje, 2020)
Conceptions and attitudes towards creativity among pre-service and in-service preschool teachers. Educators’ perceptions and attitudes towards creativity significantly determine their teaching practice. Therefore, the study aimed to examine the prevailing conceptions of creativity among pre-service and in-service preschool teachers. A multi-part questionnaire was designed and completed by two groups: preschool teachers and early childhood education students. Generally, participants demonstrated adequate theoretical knowledge in the field of creativity; however, there were minor discrepancies between the groups, which may be the result of some implicit beliefs about creativity and the perception of their role in supporting creativity of preschool children.